PELATIHAN TARTIL AL-QUR’AN BAGI LANSIA: TRANSFORMASI SPIRITUAL DAN SOSIAL DI PERUMAHAN BUMI MAS TULUNGAGUNG - Badruzaman, Abad (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2023)
The Tartil Al-Qur’an training for the elderly is part of religious education aimed at improving their ability to read the Qur’an correctly according to the rules of tajweed. This study aims to analyze the spiritual and social transformation experienced by the elderly in Perumahan Bumi Mas Tulungagung through the Tartil Al-Qur’an training program conducted at Masjid Jami’ Ar Royyan. The research employs a qualitative approach using observation, interviews, and documentation techniques involving training participants, facilitators, and mosque administrators. The findings indicate that the program positively impacts the quality of worship, religious understanding, and psychological well-being of the elderly. Additionally, it strengthens social interactions among participants and reduces the risk of social isolation. However, several challenges remain, such as the elderly’s physical and cognitive limitations, a lack of competent facilitators trained to teach older adults, and insufficient learning resources tailored to their needs.